The Effect of Profit-Sharing Financing on the Financial Performance of Islamic Banks - Argantara, Zaid Raya; Fitriyah, Nabilatul (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research aims to determine the effect of profit sharing financing, namely mudharabah financing and musyarakah financing, on the financial performance of BCA Syariah Bank with profits in the form of a predetermined profit sharing ratio and losses fully borne by the bank for Mudharabah financing. This research uses a quantitative approach with multiple linear regression techniques which aims to test the hypotheses that have been established. The type of data used is secondary data which indirectly provides data to data collectors. The data analyzed in this research are the Financial Reports for Mudharabah Financing and Musyarakah Financing of BCA Syariah Bank per Quarter of 2014-2021. Data collection techniques use documentation from the official BCA Syariah website. The independent variable in this research is profit sharing financing, namely Mudharabah Financing (X1) and Musyarakah Financing (X2) and the dependent variable is Return on Assets (Y). The data analysis technique used is multiple linear regression analysis using the SPSS 25 application. The research results show that mudharabah financing has a positive and significant effect on ROA. Musyarakah financing has no positive and insignificant effect on ROA. Simultaneously mudharabah financing and musyarakah financing have a positive and significant effect on ROA.